Household factors influencing cockroach infestations and helminth parasites: Insights from a rural community in Guatemala - Wendy C. Hernández-Mazariegos; Felipe I. Torres; Manuel Rodríguez; Christian M. Ibáñez; Luis E. Escobar; Federico J. Villatoro (PLoS ONE, 2026)
Cockroaches are vectors of pathogens and parasites that pose public health risks, especially in developing countries with poor hygiene and inadequate infrastructure. This study aimed to identify the household factors associated with the occurrence of cockroaches and the helminth parasites they carry in a rural community. Data on household infrastructure, presence of domestic animals, and insect control methods were collected from 70 households in rural Guatemala. Cockroaches were captured using traps and manually. A Generalized Linear Mixed Model revealed that households with concrete roofs had 94% lower abundance of cockroaches than those with metal sheet roofs, while the presence of cats increased cockroach abundance by 2.6 times (p < 0.05). Six genera of helminths, including the acanthocephalan zoonotic parasite Moniliformis moniliformis , were identified, marking the first report of such parasites in household cockroaches in Guatemala. These results highlight the need for improved housing infrastructure and integrated pest management strategies to mitigate the risks associated with cockroach-borne parasites in vulnerable communities.